Mascarapion, a new genus of the Apioninae (Coleoptera, Curculionoidea) from the Mascarene Islands - Wanat, Marek; Poussereau, Jacques (Zootaxa, 2019)
A new genus, Mascarapion, is erected, endemic to the Mascarene Archipelago. Three species are included as new combinations: M. mauritii (Beguin-Billecocq, 1905), M. roudieri (Richard, 1957) and M. richardi (Alonso-Zarazaga, 1983). Mascarapion richardi is given a new status of distinct species, its morphological differences from M. roudieri are described. The problematic placement of the new genus in existing apionine tribes is discussed.